Stigma Terkait Perselingkuhan dalam Perspektif Pelakor - Rosjayani, Annisa Pratiwi; Idrus, Nurul Ilmi (Emik, 2024)
In recent years, there are two terms related to infidelity, namely pelakor, a label that is given to women who snatch someone’s husband and pebinor, a label that is given to men who snatch someone’s wife. However, the term pelakor is more popular than pebinor, either in real life or in social media. This is also the case for stigma. Stigma to pelakor is more popular than stigma associated with pebinor. While the existing literatures on infidelity focus more on stigma toward pelakor on social media, little [if any], study deals with stigma towards pelakor from the perspective of pelakor themselves. This article fills this gap. This qualitative research was conducted in Makassar. There are five pelakor who get involved in this study. Data collection was carried out using in-depth interview and observation through social media. The research shows that the reasons why women snatch someone’s husband are economic needs, frequency of encounters, and rekindled love (CLBK). The process of becoming a pelakor often begins through social media, workplace interactions, or introduced by friends. In the perspective of pelakor, the stigma against them includes labels such as women without self-respect, cheap women, love in love, and immoral women, reflecting society's negative perceptions towards pelakor. However, pelakor themselves respond to this stigma in various ways, ranging from feeling of shame and desiring for self-improvement, to behave indifference toward social judgment, reflecting their personal autonomy over their life choices. It is argued in this article that while pelakor realised that they are stigmatised and ruin someone’s marriage, no one immediately ends their relationship. Pelakor even “enjoy” the affair and don’t care what people say about it.